2020
DOI: 10.1007/s00396-020-04734-0
|View full text |Cite
|
Sign up to set email alerts
|

The toolbox of porous anodic aluminum oxide–based nanocomposites: from preparation to application

Abstract: Anodic aluminum oxide (AAO) templates have been intensively investigated during the past decades and have meanwhile been widely applied through both sacrificial and non-sacrificial pathways. In numerous non-sacrificial applications, the AAO membrane is maintained as part of the obtained composite materials; hence, the template structure and topography determine to a great extent the potential applications. Through-hole isotropic AAO features nanochannels that promote transfer of matter, while anisotropic AAO w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 140 publications
0
12
0
Order By: Relevance
“…The anodic aluminum oxide (AAO) templates were prepared by the second anodization process. , First, sheets of aluminum (Al) with sizes of 1 × 4 cm 2 were obtained by cutting Al foils. Then, the Al sheets were cleaned sequentially by isopropyl alcohol, acetone, and deionized water for 10 min under an ultrasonic bath.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The anodic aluminum oxide (AAO) templates were prepared by the second anodization process. , First, sheets of aluminum (Al) with sizes of 1 × 4 cm 2 were obtained by cutting Al foils. Then, the Al sheets were cleaned sequentially by isopropyl alcohol, acetone, and deionized water for 10 min under an ultrasonic bath.…”
Section: Methodsmentioning
confidence: 99%
“…In the past years, arrays of polymer nanomaterials have received significant attention due to their special properties and potential applications in various fields, such as sensors, supercapacitors, and solar cell devices. To make arrays of polymer nanomaterials, different methods have been investigated, such as the template method, the nanoimprinting method, and the photolithography method. Compared with other methods, the template method is often chosen considering its versatility and simplicity . Anodic aluminum oxide (AAO) membrane is usually applied in the template-based approach. , Utilizing the second anodization process, AAO templates with highly regular nanopores can be prepared .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a massive amount of literature to precisely control the geometrical features of the PAA such as the pore cell size, pore diameter, interpore distance, oxide pore thickness at the bottom of the pores, porosity and circularity of the pores, making the PAA an outstanding platform for the synthesis of nanostructures. An exhaustive overview of the different possible architectures is given in recent reviews focused on the developments of nano porous alumina templates [ 38 , 40 , 43 , 82 ].…”
Section: Anodized Anodic Aluminamentioning
confidence: 99%
“…Recent developments in nanotechnology have demonstrated the potential of aluminum oxide or alumina (Al 2 O 3 ) for various applications due to its good chemical stability, wide band gap, and biological compatibility. Special attention is drawn to alumina in aqueous environments, as the behavioral understanding of this solid–liquid interface is crucial for dielectric nanocomposites, water filtration, drug delivery, biosensing devices, combustion, among others. In particular, the new developments in anodic alumina membranes, enabled by the progress in nanofabrication techniques, could be beneficial for filtration and separation of molecules, cells, or proteins, and evaporation in thermal management applications, see Figure (a). Characterizing and tuning the inner nanopore geometry and electrostatic properties in alumina membranes facilitate molecular filtration, , while the interplay between the nanopore surface and the absorbed liquid thin film is critical for the evaporation performance . It has been suggested that most of the interfacial transport (specifically momentum and thermal) is strongly influenced by a thin layer, which usually encompasses no more than a few nanometers from the interfacial region. , Due to the reduced scale, the thickness of this region hinders accurate probing using the current experimental capabilities; therefore, atomistic-level simulations can provide useful insight into the interface and transport properties.…”
Section: Introductionmentioning
confidence: 99%